2015
DOI: 10.1192/pb.bp.114.047043
|View full text |Cite
|
Sign up to set email alerts
|

Mental health clustering and diagnosis in psychiatric in-patients

Abstract: Aims and method This paper investigates the relationship between cluster (Mental Health Clustering Tool, MHCT) and diagnosis in an in-patient population. We analysed the diagnostic make-up of each cluster and the clinical utility of the diagnostic advice in the Department of Health’s Mental Health Clustering Booklet. In-patients discharged from working-age adult and older people’s services of a National Health Service trust over 1 year were included. Cluster on admission was compared with primary diagnosis on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…The validity of both approaches can be challenged but it is also important to avoid conflating issues of validity with utility (Kendell & Jablensky, 2003). In this way, the two systems should be viewed as complimentary (Trevithick, Painter, & Keown, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The validity of both approaches can be challenged but it is also important to avoid conflating issues of validity with utility (Kendell & Jablensky, 2003). In this way, the two systems should be viewed as complimentary (Trevithick, Painter, & Keown, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Although CTOs have been recommended as a method for improving adherence and patient safety, patients treated under CTOs feel more coerced. 6 The use of CTOs has been much higher than was initially anticipated, 7,8 and has increased considerably since they were first introduced. 8,9 Concerns have been raised about greater use of compulsion amongst people from ethnic minority communities.…”
Section: Aims and Methodsmentioning
confidence: 99%
“…6 The use of CTOs has been much higher than was initially anticipated, 7,8 and has increased considerably since they were first introduced. 8,9 Concerns have been raised about greater use of compulsion amongst people from ethnic minority communities. [10][11][12] Data submitted to NHS Digital in 2016 indicated that Black or Black British patients were almost nine times more likely to be treated on a CTO than White British patients.…”
Section: Aims and Methodsmentioning
confidence: 99%
“…However, two of the most popular measures used in the USA to inform resource allocation (the ICAP and the DDP) have a similar focus and, parallel work in the UK's mainstream mental health services (see Trevithick, Painter, & Keown, 2015) has found considerable utility from this approach. Additionally, our multi-site project would have almost certainly encountered the geographical variation in current service provision that may lead to distorted clinician-ratings of support needs (Acheson, 1978).…”
Section: Discussionmentioning
confidence: 99%